Green Synthesis and Comprehensive Characterization of Silver Nanoparticles Using Lawsonia inermis Extract for Biological Applications - K., Nithya; Imthiyas, A. Mohammed; Jagadeeswari, S.; Vidya, P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This research focuses on the production, characterization, and application of silver nanoparticles (AgNPs) for biomedical research. An eco-friendly extracellular biosynthetic method was employed, utilizing aqueous leaf extracts of Lawsonia inermis (Henna) as reducing agents. The synthesized AgNPs were characterized using UV-Vis spectroscopy, showing an absorption peak at 424 nm. FT-IR analysis was conducted to identify chemical groups present in nanoparticles. TEM and SEM analyses revealed that AgNPs were spherical and ranged in size from 10 to 50 nm. Staphylococcus aureus, Klebsiella, Salmonella, and Escherichia coli were inhibited by the green-synthesised AgNPs. Penicillium, Aspergillus niger, Aspergillus flavus, and Fusarium showed antifungal activity, forming zones of inhibition. Furthermore, the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values were found to be 75 mg/ml (Escherichia coli ATCC25922) and the MIC value was 50 mg/ml for the same strain. These nanoparticles demonstrated significant anti-inflammatory activity and dose-dependent cytotoxicity against A549 lung cancer cells. As a result of the synthesized nanoparticles, strong antioxidant activity was observed. The results suggest that plants can be effectively used as a resource for the production of silver nanoparticles. Such particles have potential applications in numerous fields such as biomedical research and nanotechnology.